2019
DOI: 10.1016/j.jcbs.2019.04.001
|View full text |Cite
|
Sign up to set email alerts
|

ACT for sleep - Internet-delivered self-help ACT for sub-clinical and clinical insomnia: A randomized controlled trial

Abstract: This is a self-archived version of an original article. This version may differ from the original in pagination and typographic details.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 44 publications
5
24
1
Order By: Relevance
“…The first one, which compared CBT with ACT in 31 patients, found equivalent effects of both therapies on insomnia, anxiety, beliefs about sleep and experiential avoidance (Rafihi-Ferreira et al, 2019). The second study compared unguided internet-delivered ACT with a WCL in 86 patients (mainly with subclinical insomnia) and found improvement in the ACT group with small to moderate effect size (Lappalainen et al, 2019). None of these studies evaluated the im- .00 *** although a quarter of participants did not apply sleep restrictions and only half of them applied stimulus control, most of them still reported sleep improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one, which compared CBT with ACT in 31 patients, found equivalent effects of both therapies on insomnia, anxiety, beliefs about sleep and experiential avoidance (Rafihi-Ferreira et al, 2019). The second study compared unguided internet-delivered ACT with a WCL in 86 patients (mainly with subclinical insomnia) and found improvement in the ACT group with small to moderate effect size (Lappalainen et al, 2019). None of these studies evaluated the im- .00 *** although a quarter of participants did not apply sleep restrictions and only half of them applied stimulus control, most of them still reported sleep improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In an observational cohort study, an ACT treatment for chronic pain was associated with improved sleep (Daly‐Eichenhardt et al., 2016). More recently, two randomized studies (face‐to‐face pilot and unguided internet‐delivered ACT) reported promising results in insomnia‐related outcomes (Lappalainen et al., 2019; Rafihi‐Ferreira et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These flexibility processes gradually interacting with one another produce greater psychological flexibility or inflexibility processes interact with one another and cause psychopathology. In other words, ACT is about providing room for pain and helping clients to move forward toward chosen values to create a meaningful life and enhancing the quality of life and/or addressing issues, which is the main duty of mental health providers (Tanhan, 2018 (Kyllönen, Muotka, Puolakanaho, Astikainen, Keinonen, & Lappalainen, 2018;Pleger, Treppner, Diefenbacher, Schade, Dambacher, & Fydrich, 2018;Proctor, Moghaddam, Evangelou, & Das Nair, 2018;Puolakanaho et al, 2019), obsessive compulsive disorder (Rohani, Rasouli-Azad, Twohig, Ghoreishi, Lee, & Akbari, 2018;Twohig et al, 2018), cancer related psychological issues (González-Fernández, Fernández-Rodríguez, Paz-Caballero, & Pérez-Álvarez, 2018;McClure, Bricker, Mull, & Heffner, 2019;Wells-Di Gregorio et al, 2019), chronic pain (Razavi, Aboalghasimi, Akbari, & Nadirinabi, 2019), migraine (Grazzi, Bernstein, Raggi, Sansone, Grignani, Searl, & Rizzoli, 2019), sleep issues (Päivi, Sitwat, Harri, Joona, & Raimo, 2019;Wiklund, Linton, Alföldi, & Gerdle, 2018), suicide prevention (Bazley & Pakenham, 2019;Ducasse et al, 2018), psychosis (Spidel, Daigneault, Kealy, & Lecomte, 2019). In addition, online versions of ACT RCTs were conducted to address various issues including pain (Lin et al, 2017;Simister, Tkachuk, Shay, Vincent, Pear, & Skrabek, 2018), depression (Molander et al, 2018), stress (Hofer et al, 2018), and smoking (Bricker, Mull, McClure, Watson, & Heffner, 2018).…”
Section: Tanhan 200mentioning
confidence: 99%
“…In two previous pilot studies ACT interventions for eight weeks improved subjective sleep quality among four and 15 individuals with insomnia [ 48 , 49 ]. An ACT intervention improved sleep patterns in adults with insomnia (n = 43), compared to a wait-list condition (n = 40) [ 50 ]. ACT-interventions improved subjective sleep among ten individuals with insomnia poorly responding to CBT-interventions before [ 51 ].…”
Section: Introductionmentioning
confidence: 99%